Failure analysis of helical gear pinion. (2022) - Ghosh, Debashis; Mondal, Abhijit; Hussain, Nasir; Kumar De, Sanjib; Ray, Subrata; Subramanian, Chidambaram
Abstract: The pinion in helical gear has been failed after 20 days of service in engineering industry, which processes grinding ball media. The failure have reduced production margin of engineering industry and root cause of failure was identified. The pinion was made from EN24 steel supplied in hardened and tempered conditions. However, inclusion in steel have initiated fatigue crack and resulted in failure. EDX mapping evidenced that inclusion was oxide in nature. Metallography confirmed that steel contain tempered martensite structure along with oxide inclusions. It is recommended to select clean steel in gear applications to avoid similar kind of premature failure.